THE MODERATING ROLE OF PHILADELPHIA FINANCIAL SERVICE COMPANIES' PERFORMANCE IN THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND ENVIRONMENTAL SUSTAINABILITY - Shahad Salim (Transpublika Publisher, 2024)
The current study delves into the complex relationship between corporate governance, financial performance, and societal responsibility within the financial service sector in Philadelphia. Drawing on data from 85 financial organizations, the research explores how different corporate governance practices impact firm value and perceptions of environmental sustainability. The findings reveal that strong corporate governance practices tend to enhance societal obligations, but do not consistently lead to perceptions of increased environmental stewardship. This emphasizes the intricate nature of governance impacts within the financial service domain, where traditional performance metrics may not fully capture the sector's operational dynamics. Additionally, empirical evidence indicates that the relationship between corporate governance effectiveness and corporate social responsibility is influenced by firm size, highlighting the need for governance frameworks tailored to specific contexts. The study advocates for the development of performance indicators that better align with the operational realities and societal expectations of financial service entities. Furthermore, the research emphasizes the role of trust-based indicators in building stakeholder confidence and institutional trust. By focusing on Philadelphia's financial service enterprises, the study provides new insights into the individual dimensions of corporate governance and their implications for environmental sustainability. It underscores the importance of adaptive governance structures that not only ensure financial stability but also promote a corporate culture of accountability and environmental stewardship. This study is groundbreaking in its exploration of the relationship between corporate governance, financial performance, and CSR in the context of Philadelphia's financial services.